Adaptive reuse process of the Historic Urban Landscape post-Covid-19. The potential of the inner areas for a “new normal” - Maria Rita Pinto; Serena Viola; Katia Fabbricatti; Maria Giovanna Pacifico (Vitruvio: International Journal of Architectural Technology and Sustainability)
Often in the past, the great disasters (environmental calamities, earthquakes, epidemics) activated unexpressed energies, triggering transformations of the built environment, able to give rise unexpected conditions of economic, cultural and social development. The fragility of settlement systems in the face of unexpected threats brings out the need for a new planning, changing our gaze on the city. The new framework of needs drawn by the pandemic and the renewed sensitivity towards the combination of health – sustainability, rekindle the spotlight on inner areas. These emerged as "reservoirs of resilience", areas to look at, in order to reach an eco-systemic balance. The aim of the paper is to return an experience of adaptive reuse of the Historical Urban Landscape in an inner area of Southern Italy, where the needs of health and safety of the community are integrated with the transmission of the built heritage to future generations. The goal is the promotion of inclusive prosperity scenarios, towards the so-called "new normality". Starting from an in-depth literature review on the cases of pandemics in history and the strategies implemented, the research identifies health security requirements at the scale of the Historical Urban Landscape and design solutions aimed at reactivating lost synergies between communities and places.